African Women’s Envisioning of Mission and Theological Education in the 21st Century and Beyond - Mombo, Esther (2022)
Esther Mombo is an associate professor at St. Paul's University in Limuru, Kenya, where she was previously deputy vice chancellor (Academics). She teaches church history and theologies from women’s perspectives. She works closely with the Programme for Christian and Muslim Relations in Africa and is a member of the Circle of Concerned African Women Theologians. Her areas of service include networking among Christian and Muslim women leaders on issues of dialogue. She has previously served on the Inter-Anglican Doctrinal and Theological Commission. Mombo earned her BD from St. Paul's United Theological College, MPhil from Trinity College Dublin, and PhD at Edinburgh University.
free